The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s11010-005-9001-x
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Effects of Ketogenic Diet in Obese Subjects with High Cholesterol Level

Abstract: This study shows the beneficial effects of ketogenic diet following its long term administration in obese subjects with a high level of total cholesterol. Moreover, this study demonstrates that low carbohydrate diet is safe to use for a longer period of time in obese subjects with a high total cholesterol level and those with normocholesterolemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
2
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(124 citation statements)
references
References 40 publications
6
111
2
5
Order By: Relevance
“…A number of studies (10,11,51) have shown that dieting subjects eating a high-fat, low-carbohydrate diet tend to lose more weight more rapidly than subjects eating a low-fat, high-carbohydrate diet, leading to the speculation that high-fat diets might enhance weight loss by attenuating the decrease in energy expenditure typically seen with dieting. However, such an effect has not been demonstrated in either humans or rodents.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies (10,11,51) have shown that dieting subjects eating a high-fat, low-carbohydrate diet tend to lose more weight more rapidly than subjects eating a low-fat, high-carbohydrate diet, leading to the speculation that high-fat diets might enhance weight loss by attenuating the decrease in energy expenditure typically seen with dieting. However, such an effect has not been demonstrated in either humans or rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple authors [29] highlighted the misleading nature of this article, pointing out that insufficient detail was provided to enable correct evaluation of the case report. Further criticism of Atkins style diets focuses on the consequences for cardiovascular health, since many of these diets contain high levels of saturated fat [8]. In vivo, dietary fat is transported to the liver by chylomicrons, where triglycerides are repackaged and secreted as nascent VLDL, which, via.…”
Section: The Atkins Dietmentioning
confidence: 99%
“…However, two recent studies have shown that the longterm use of a low-carbohydrate diet (6-14 months) has a favorable effect on serum cholesterol, lipoprotein subfractions, and high-sensitivity C-reactive protein despite the increased intake of dietary fat. 8,9 However, the use of a low-carbohydrate diet does result in increased serum levels of chylomicrons and chylomicron remnants, both of which are capable of contributing to vascular plaque formation. 8 A theoretical concern exists that increased hepatic lipid oxidation as a result of decreased dietary carbohydrate intake could exacerbate the inflammatory milieu via enhanced freeradical production.…”
mentioning
confidence: 99%